Performance of a Histidine Rich Protein-2 Based (First Response) and a p-Lactate Dehydrogenase-based (Optimal) Rapid Diagnostic Test for Diagnosis of Malaria in Patients With Pediatric Sickle Cell Disease. (26th November 2021) - Adjei, George O; Sulley, Abdul M; Goka, Bamenla Q; Enweronu-Laryea, Christabel; Renner, Lorna; Alifrangis, Michael; Kurtzhals, Jorgen A L
Abstract: Background: Rapid diagnostic tests (RDTs) have been extensively evaluated and play an important role in malaria diagnosis. However, the accuracy of RDTs for malaria diagnosis in patients with sickle cell disease (SCD) is unknown. Methods: We compared the performance of a histidine rich protein 2 (HRP-2)-based RDT (First Response) and a lactate dehydrogenase (LDH)-based RDT (Optimal) with routine microscopy as reference standard in 445 children with SCD and an acute febrile illness in Accra, Ghana. Results: The overall sensitivity, specificity, and positive and negative predictive values of the HRP-2-based RDTs were 100%, 95.7%, 73.8%, and 100%, respectively. Comparable values for the LDH-based RDTs were 91.7%, 99.5%, 95.7%, and 99.0%, respectively. A total of 423 results were true in both tests, 1 result was false in both tests, 16 results were false in the HRP-2 test only, and 5 were false in the LDH test only (McNemar test, P = .03). At follow-up, 73.7% (28/38), 52.6% (20/38), 48.6% (17/35), and 13.2% (5/38) of study participants were HRP-2 positive on days 14, 28, 35, and 42, respectively, compared with 0%, 2.6% (1/38), 2.9% (1/35), and 2.6% (1/38) for LDH. Conclusion: The HRP2-based RDT fulfilled World Health Organization criteria for malaria diagnosis in patients with SCD and may provide diagnostic evidence for treatment to begin in cases in which treatment would otherwise have begun presumptively based on symptoms, whereas LDH-based RDTs may be more suitable as a confirmatory test in low-parasitemic subgroups, such as patients with SCD. Abstract : We studied the reliability of rapid diagnostic tests for malaria in 445 febrile patients with sickle cell disease in Ghana. HRP2-based tests had 100% sensitivity compared with 91.7% for LDH-based tests, whereas specificity was lower (95.7% vs. 99.5%) for HRP2-based tests.